Aspirin might reduce the incidence of breast cancer: An updated meta-analysis of 38 observational studies. Issue 38 (18th September 2020) - Cao, Yueqing; Tan, Aihua
Abstract: Background: Many epidemiologic studies were performed to clarify the protective effect of regular aspirin use on breast cancer risks, but the results remain inconsistent. Here, we conducted an updated meta-analysis of 38 studies to quantitatively assess the association of regular aspirin use with risk of breast cancer. Method: We performed a bibliographic database search in PubMed, Embase, Web of Science, Cochrane library, Scopus, and Google Scholar from January 1939 to December 2019. Relative risk (RR) estimates were extracted from eligible case–control and cohort studies and pooled using a random effects model. Subgroup analysis was conducted based on study design, aspirin exposure assessment, hormone receptor status, menopausal status, cancer stage as well as aspirin use duration or frequency. Furthermore, sensitivity and publication bias analyses were performed. Results: Thirty eight studies of 1, 926, 742 participants involving 97, 099 breast cancer cases contributed to this meta-analysis. Compared with nonusers, the aspirin users had a reduced risk of breast cancer (RR = 0.91, 95% confidence interval [CI]: 0.87–0.95, P value of significance [ P sig ] < .001) with heterogeneity ( P value of heterogeneity [ P het ] < .001, I 2  = 82.6%). Subgroup analysis revealed a reduced risk in case–control studies (RR = 0.83, 95% CI: 0.78–0.89, P sig  < .001), in hormone receptor positive tumors (RR = 0.91, 95% CI: 0.88–0.94, P sig  < .001), in situ breast tumors (RR = 0.79, 95% CI: 0.71–0.88, P sig  < .001), and in postmenopausal women (RR = 0.89, 95% CI: 0.83–0.96, P sig  = .002). Furthermore, participants who use aspirin for >4 times/wk (RR = 0.88, 95% CI: 0.82–0.96, P sig  = .003) or for >10 years (RR = 0.94, 95% CI: 0.89–0.99, P sig  = .025) appeared to benefit more from the reduction in breast cancer caused by aspirin. Conclusions: Our study suggested that aspirin use might be associated with a reduced risk of breast cancer, particularly for reducing the risk of hormone receptor positive tumors or in situ breast tumors, and the risk of breast cancer in postmenopausal women. Abstract : Supplemental Digital Content is available in the text